Low Serum Sex Hormone-Binding Globulin Associated with Insulin Resistance in Men with Nonalcoholic Fatty Liver Disease - Ye, Juan; Yao, Ziting; Tan, Aihua; Gao, Yong; Chen, Yingchun; Lin, Xinggu; He, Rongquan; Tang, Ruiqiang; Hu, Yanling; Zhang, Haiying; Yang, Xiaobo; Wang, Qiuyan; Jiang, Yonghua; Mo, Zengnan (Hormone and Metabolic Research, 2017)
The presence of nonalcoholic fatty liver disease (NAFLD) is a strong risk predictor for type 2 diabetes (T2D). A reduction in sex hormone-binding globulin (SHBG) is associated with NAFLD. Low SHBG is also associated with insulin resistance (IR). However, very limited data are available for the association of SHBG and IR in patients with NAFLD. The study aims to clarify the association between SHBG and IR in patients with NAFLD. In this cross-sectional study, 334 men with NAFLD were recruited. SHBG, total testosterone, free testosterone, total cholesterol, triglyceride, insulin, and glucose concentrations were measured. Homeostatic model assessment (HOMA)-IR and HOMA-β were calculated. Spearman’s correlations and multiple linear regressions were used to analyze the association between SHBG and IR. Men with moderate-severe NAFLD had higher waist circumference, BMI, total cholesterol, triglyceride, insulin, HOMA-IR, HOMA-β, and free testosterone, but lower SHBG than the mild NAFLD. The moderate-severe NAFLD group exhibited higher HOMA-IR (2.38±1.35 vs. 4.16±2.84, p<0.001) and lower SHBG (25.89±11.89 vs. 30.13±12.97 nmol/l, p<0.001) than the other group. SHBG value was negatively correlated with insulin, and HOMA-IR, but was not significantly correlated with glucose and testosterone. The multiple linear regression analysis showed that SHBG was significantly associated with insulin (β=− 0.241, p<0.001), and HOMA-IR (β=− 0.229, p<0.001), even adjusting for potential confounders. In conclusion, low serum SHBG is associated with IR in men with NAFLD.
Keywords: insulin resistance; HOMA-IR; SHBG; NAFLD